Socialization and Assistance in the Use of Social Media by Laundry MSMEs - Puji Aledya Angguna; Hasyim As’ari (PT FORMOSA CENDEKIA GLOBAL, 2025)
This community service activity aims to improve the ability and awareness of MSME actors in utilizing social media as an effective promotional tool. Activities are carried out through, interviews, socialization, mentoring, and evaluation with the direct meeting method. This activity was carried out in several sessions in April 2025 with a focus on training practitioners in content creation, social media management and the application of digital marketing strategies. The results of this activity show an increase in the understanding and skills of laundry business actors in using social media platforms such as Instagram, Facebook, and TikTok to promote services, build interactions with customers, and expand market reach. This activity contributes to increasing the competitiveness of MSMEs in the digital era.